An Analytically Defined Fire‐Suppressing Foam Formulation for Evaluation of Fluorosurfactant Replacement. Issue 5 (31st July 2018) - Hinnant, Katherine M.; Giles, Spencer L.; Snow, Arthur W.; Farley, John P.; Fleming, James W.; Ananth, Ramagopal
Abstract: A 4‐component, analytically defined, reference fluorosurfactant formulation (Ref‐aqueous film forming foam [AFFF]) composed of 0.3% fluorocarbon‐surfactant concentrate (Capstone 1157), 0.2% hydrocarbon‐surfactant concentrate (Glucopon 215 UP), and 0.5% diethylene glycol mono butyl ether by volume in distilled water was found to have rapid fire extinction comparable to a commercial AFFF in tests conducted on a bench scale and a large scale (28 ft 2, part of US Military Specification, MIL‐F‐24385F). The Ref‐AFFF was analytically characterized to provide the identity and quantity of the chemical structures of the surfactant molecules that were lacking for commercial AFFF formulations. To arrive at an acceptable Ref‐AFFF formulation, 3 candidate formulations containing different hydrocarbon surfactants in varying amounts were evaluated and ranked relative to a commercial AFFF using a bench‐scale fire‐extinction apparatus; varying the hydrocarbon surfactant was found to affect the fire‐extinction time. The ranking was confirmed by the large‐scale tests suggesting that the bench‐scale apparatus is a reasonable research tool for identifying surfactants likely to succeed in the large‐scale test. In the future, replacing the fluorocarbon surfactant with an alternative surfactant in the Ref‐AFFF enables a direct comparison of fire extinction and environmental impact to identify an acceptable fluorine‐free formulation.